(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article deals with the organization of the educational process, the essence of the state program "First Step", the interests of the preschool children, their potential, individual mental and physical characteristics, spiritual and cultural needs, as well as the need for cultural protection. and each side of development is reflected in the acquisition of social experience.